Information and educational environment of higher education institutions as a foundation for the formation of the information and communication culture of future specialists - Klieba, Anna; Shcherbak, Iryna; Tupytsia, Alina (My University, 2022)
At the current stage, the main goal of higher education is the improvement of the information and educational environment, in which each student will build a personal trajectory of achieving individual self-realization in the chosen specialty and in society. The content of the concepts «information and communication culture», «interactive information and educational environment», «digital educational resources» has been clarified. The essence of the information and communication culture of higher education applicants is determined. The structure of information and communication culture, which includes value-motivational, information-technological and communicative components, is considered. The concepts of information and communication orientation and «information and communication competence» as components of information and communication culture are analyzed. The stages of involvement of education seekers in information and communication activities are determined. It has been proven that information and communication activities are carried out in the joint productive activity of teachers and students in higher education institutions. The role of the information and educational environment in the educational process of the institution of higher education, the role of the latest digital technologies, electronic training courses and requirements for them, methodical recommendations for using the resources of the information and education environment in the formation of the information and communication culture of future specialists as a component of professional culture are substantiated. The creation of an information and educational environment involves the development of software and technical tools (modules, services, databases), the development of the structure and levels of information and communication culture.
Klieba А. Information and educational environment of higher education institutions as a foundation for the formation of the information and communication culture of future specialists / A. Klieba, I. Shcherbak, A. Tupytsia // Enrichment of the pedagogical cluster of educational services : international collective monograph / edited by G. F. Ponomarova, A. A. Kharkivska, L. O. Petrychenko and other; Municipal Establishment «Kharkiv Humanitarian Pedagogical Academy» of Kharkiv Regional Council : Publishing house OKTAN PRINT s.r.o., 2022. – P. 348–362
Keywords: інформаційно-освітнє середовище, освітній процес, заклад вищої освіти, здобувач вищої освіти, інформаційно-комунікаційна культура, інформаційно-комунікативна спрямованість, інформаційно-комунікативна компетентність; information and educational environment educational process, institution of higher education, students of higher education, information and communication culture, information and communicative orientation, information and communicative competence.